Section for Residents and Fellows Leaders: Where Are They Now?. (23rd August 2013) - Wilson, Meghan N.; Roby, Brianne B.; Deckard, Nathan A.; Carter, John M.; Yoo, Estelle S.; Kelley, Kanwar; Raol, Nikhila M.
Abstract : Objectives: 1) Look at the experiences of prior governing council (GC) members of the American Academy of Otolaryngology (AAO) Section for Residents and Fellows (SRF), and 2) assess the impact of early Academy involvement. Methods: Survey of all prior members of the AAO SRF GC. Results: The AAO‐SRF has elected 52 GC members since its 2003 inception. Ten members are currently in training, and no data were obtained for 3. The remaining 38 prior GC members were analyzed. Each member served an average of 1.5 years (terms ranged 1 ‐ 3 years). The mean time since completion of training to present is 4.1 years (range 0 ‐ 10 years). A subspecialty fellowship was pursued in 86%, with 92% matching into their fellowship field of choice. Fifty‐seven percent practice in an academic setting, with 3 members advancing to a subspecialty division director within their department. All prior GC members are current AAO members. Over half (59%) have served on an AAO committee, and most are frequent attendees of the annual meeting. When asked, "What did being on the SRF GC do for you?", the most common responses included understanding the importance of the AAO and involvement in it, networking, and leadership experience. Conclusions: All prior SRF GC members felt involvement in the SRF GC was a beneficial experience, enabling them to gain leadership skills and a deeper understanding of the inner‐workings of our specialty. Most prior SRF GC members have pursued fellowship training and remain involved in the Academy.